ANALISIS PREFERENSI MAHASISWA FMIPA USU TERHADAP PRODUK HANDPHONE DENGAN MENGGUNAKAN ANALISIS KONJOIN - Rifalin Delustia Purba; Open Darnius; Pasukat Sembiring (Universitas Sumatera Utara, 2013)
This research is aimed to analyze the students preference of handphone in The Faculty of Mathematics and Natural Sciences, University of Sumatera Utara. The method that is used in this research is conjoint analysis. The data that is used in this research is the primary data obtained by distributing questionnaires to students of The Faculty of Mathematics and Natural Sciences, University of Sumatera Utara for class 2008 to 2011. The results revealed that the most attractive factor for students in this research are the existence of mp3 player and internet service. The ideal concept of handphone according to the preference of students is Blackberry, with the price less than Rp 1.500.00,- ; Numeric Keypad navigation, 1-5 Megapixel, with small screen (less than 2 inch), White, and the existence of internet service and mp3 player.